A SINGLE-PHASE ACTIVE DEVICE FOR POWER QUALITY IMPROVEMENT OF LINEAR AND NON-LINEAR LOAD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Electricity is one of the basic requirements of human beings, which is widely used for domestic, industrial, commercial and agricultural purposes. There is great demand for electricity and it is increasing day by day, but now a day what happened actually the method for accessing the data from the energy meter and billing is not up to the mark as well as it is time consuming. It is also required a huge manpower to complete this process. Because of that to reduce this huge manpower as well as complications, we exists this system. Our system provides the electricity readings on an LCD screen as well as can SMS this reading and cost in rupees to the user. A GSM modem is also integrated along with the meter to send alerts to the particular consumer regarding their energy consumption. In case of failure of payment by a consumer the controller can disconnect the power supply of the consumer. A PC with a GSM receiver at the other end, which contains the database acts as the billing point.